The effect of transcrestal sinus-floor elevation without graft on the long-term prognosis of maxillary implants - Rammelsberg, Peter; Kilian, Samuel; Büsch, Christopher; Kappel, Stefanie (Journal of clinical periodontology, 2020)
Aim To evaluate the effects of (a) transcrestal sinus-floor elevation (TSFE) and (b) residual bone height on long-term implant survival. Materials and Methods Chi-squared and t tests were used for descriptive comparison of the groups. Kaplan-Meier survival curves and corresponding log-rank tests were used to investigate implant survival over time. Multivariable Cox regressions were performed for the total population and experimental group. Results A total of 634 patients received 648 implants with TSFE, while 674 implants without TSFE served as controls. Thirty implant failures occurred in the experimental group and 28 in the control group. Ten-year Kaplan-Meier survival curves for the 157 implants (24.3%) still under observation showed a probability of survival of 93.7% for the implants with TSFE and 92.9% for the 72 implants without TSFE (p = .678). The probability of 10-year survival of all implants in the experimental group decreased to 77.4% for implants placed in residual bone heights of 1-3 mm, compared with 95.7% for implant sites with bone heights of 4-6 mm and 97.6% for bone heights of >6 mm. Conclusions Transcrestal sinus-floor elevation has no negative effect on the long-term implant survival. Membrane perforation or negligible bone height, however, reduces the probability of 10-year survival.
First published: 07 March 2020
Gesehen am 11.01.2022